STUDENTS’ MOTIVATION TOWARDS SELF-REGULATED LEARNING APPLIED IN LEARNING PROCESS: A STRATEGY TO INDEPENDENT STUDENTS - Eltina Maromon; Tiarma Marpaung (JURNAL PENDIDIKAN, 2023)
An instruction should encourages, enables and guides students to prepare, ready and being able to an appropriate learning environment in reaching their successfulness, therefore a successful student builds such kinds of efforts, desires to determine or arrange positive motivation to come to good result of a learning process of him. The good result of the learning process is built by a good motivation which is related to a students’ capability to cope effectively with disturbances, a crucial part of self-regulated learning. Being a self regulated learning on online learning during pandemic era must be followed and supported by students’ own motivation. It would be intrinsic or extrinsic motivation. Realizing this condition, the writers structuring students to elaborate their own motivation for being independent students as self regulated learner in instructional event. When students are capable to pay attention, they themselves must have their own positive environment on motivation itself that allows them to reach the meaning of content material has learnt. Self-regulated students is provided to promote elements of intrinsic and extrinsic motivation in an instructional environment which enable students to meet their learning goals successfully to compete with others goals in order for getting attention and other cognitive resources. Keywords: Motivation, Self regulated learning, Independent students